Double-Blind in Light of Internet – Note on Review Processes - Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2009)
This paper analyses the credibility of author anonymity provided by double-blind review processes. It is argued that authors have strong incentives to disseminate information about their papers before publication. A sample from two economics journals, both using double-blind review processes provides evidence that author revealing information of most accepted papers is available on the Internet before the review processes are finished. The difficulty and cost of identifying authors of anonymized unpublished manuscripts are examined in an experiment where subjects are paid according to their identification performance. The vast majority of authors can be identified within 60 seconds.
Keywords: C91; D80; O30; 330; Review Process; Scientific Publication; Experiment